Forest cover enhances natural enemy diversity and biological control services in Brazilian sun coffee plantations - Medeiros, Hugo Reis [UNESP]; Grandinete, Yuri Campanholo [UNESP]; Manning, Paul; Harper, Karen A.; Cutler, G. Christopher; Tyedmers, Peter; Righi, Ciro Abbud; Ribeiro, Milton Cezar [UNESP] (Springer Nature, 2019)
Landscape structure and crop management directly affect insect communities, which can influence agriculturally relevant ecosystem services and disservices. However, little is known about the effect of landscape structure and local factors on pests, natural enemies, and biological control services in the Neotropics. We investigated how environmental conditions at local and landscape levels affect Leucoptera coffeella (insect pest), social wasps (natural enemies), and the provision of biological control services in 16 Brazilian coffee plantations under different crop management and landscape contexts. We considered microclimatic conditions, coffee plantation size, and management intensity at the local level; and forest cover, landscape diversity, and edge density at the landscape level. Pest population, wasp communities, and biocontrol services were monitored in wet and dry seasons when L. coffeella outbreaks occur. We found that the amount of forest in the surrounding landscape was more important for explaining patterns than the local environment, landscape diversity, or landscape configuration. In both seasons, L. coffeella was negatively affected by forest cover, whereas biological control and richness and abundance of social wasps increased with increasing forest cover at multiple spatial scales. Moreover, biological control was positively correlated with wasp abundance during pest outbreaks, suggesting that social wasps are important natural enemies and provide pest control services within coffee plantations. We provide the first empirical evidence that forest cover is important for the maintenance of social wasp diversity and associated pest control services in a Brazilian coffee-producing region.
Keywords: Agroecosystems; Biodiversity conservation; Coffee leaf miner; Ecosystem services; Landscape structure; Social wasps